The Effect of Work Discipline, Work Motivation, and Work Engagement on Employee Performance - Iswari, A A Esti Widya; Kurniawati, Ni Putu Ayu Tika; Dewi, A A Istri Krisna Gangga (PT. EQUATOR SINAR AKADEMIA, 2026)
The study’s aim is analyze influence from work motivation, its discipline also engagement to employee performance. Main issue raised in study is decline of employee performance as reflected in the failure of company to get its sales targets. Main focus is examine influence between these four variables in partially or simultaneous. Researcher implemented uantitative method. Its population included all employees. Saturated sampling used for this study, all 38 employees were used as research samples. Researcher collected data by both questionnaires and also observation. To analysis, multiple linear regression to processed data. Study’s findings prove work motivation, discipline, also engagement significantly influenced employee performance in partial. As addition, these variables were also proven to influenced employee performance in significant-positive term. Keywords : Work discipline, Work motivation, Work engagement, and Employee performance